Predictors of New Cerebral Microbleeds in Patients with Antiplatelet Drug Therapy - Wobith, Maria; Mayer, Christian; Belke, Marcus; Haag, Anja; Gerstner, Anja; Teepker, Michael; Strzelczyk, Adam; Werner, Rita; Hamer, Hajo; Rosenow, Felix; Menzler, Katja; Knake, Susanne (Journal of Stroke and Cerebrovascular Diseases, 2016)
Cerebral microbleeds (CMB) are associated with an increased risk for ischemic and especially hemorrhagic stroke. The aim of the present study is to identify patients at high risk for the development of new CMB after initiation of an antiplatelet drug therapy.Patients received magnetic resonance imaging (MRI) within 1 week after initiation of an antiplatelet drug treatment due to a first ischemic stroke (n = 58) and after a follow-up period of 6 months (n = 40). We documented the presence and the number of CMB at baseline and follow-up and analyzed the influence of possible risk factors including vascular risk factors, stroke etiology, and number of CMB at baseline using stepwise logistic regression and Spearman's correlation coefficient. We compared progression rates of CMB in relation to each risk factor using the Mann-Whitney U-test.The logistic regression model could correctly predict the presence of CMB in 70.7% of patients at baseline and 80% at follow-up. The model correctly identified 85% of patients with new CMB. We observed progression of CMB in 40% of the patients. The overall progression rate was .8 CMB per patient. The progression rate was significantly influenced by age more than 70 years and atherothrombotic stroke. The number of new CMB correlated significantly with the number of CMB at baseline.We found several predictors of CMB after initiation of antiplatelet drug therapy. The results help to identify patients who need closer monitoring and thorough control of risk factors in order to lower the risk of new CMB and associated complications.
EVALuna2:22489